Pan-Asianism and Japanization of Malaya: The Study of Japanese policy and its impacts on Malay community - Fathil, Fauziah (2012)
Pan-Asianism and Japanization are two conceptual terms identified with Japanese policies towards some occupied areas in East and Southeast Asia during the Pacific war period. While both have different meanings and connotations, the two are somehow related to each other as both explained the policies adopted by Japan during the war period towards people of the occupied areas. Held up as the ultimate objectives of Japan‘s drive in subduing the areas, the terms had repeatedly been articulated by Japanese leaders and officials through different means and ways. This paper aims to assess the utilization and implementation of these concepts onto Malaya by looking at the various policies designed and made in ruling over Malay community in the country. The effects of the policies and the people’s response to the policies will also be examined to understand the effectiveness of the policies and their shortcomings whenever necessary. Finally the study will attempt to highlight that while the socio-cultural impacts of the two concepts did not last, the political impacts however, are noticeable and real, leading eventually to the rise of nationalism among the Malay community against British colonial rule.